Ethics and fiqh for daily life: an Islamic outline - Haneef, Sayed Sikandar Shah (IIUM Press, 2005)
Islam is a religion at the core of which lies belief and it blossoms and perpetually grows through a code of practice consisting of legal rules and moral principles. Iman will fade if it is not sustained by ethical values and moral ideals and reinforced by legal code pf practices. This book presents some of the pertinent aspects of ethics and fiqh for everyday life which benefits non-specialists in religious studies.